The Effectiveness of Health Promotion in Reducing of Skabies In The Islamic Boarding School - Indriati, Indriati; Setyowati, Tutik; Abidin, M. Zainal (Universitas STRADA Indonesia, 2019)
Background: The results of interviews with the School Health Unit in 3 Islamic boarding schools (pesantren) in Blora City District showed that 75% -90% of santri had been exposed to scabies.Purpose: This study aims to analyze the effectiveness of health promotion in reducing the incidence of scabies.Methods: Interventions in the form of health promotion (counseling, and community development). Independent health promotion variables, the dependent variable is the incidence of scabies, the variable between knowledge, attitude, and behavior. The research design is quasi-experimental one group (pretest-posttest). Place of research for Islamic boarding schools in Blora City District. The research population of the santri was a sample of students in grades 8 and 9. Proportional random sampling sampling technique. The intervention is carried out on August, 26, 2018 until October, 23, 2018.Result: Mean knowledge, attitude, and behavior before intervention 69.76; 69.86; 54.65. After intervention 87,18; 88.06; 63.35. P Value of knowledge, attitudes, and behavior = 0.00; meaning that there are differences in knowledge, attitudes, and behaviors before and after the intervention. Before the intervention students were exposed to 128 scabies (75.29%) and after intervention 5 people (2.94%). There is a difference in the proportion of scabies before and after the intervention with P Value = 0.00.Conclusion: Health promotion is effective in reducing the incidence of scabies in Islamic boarding schools in Blora City